Formulation and Evaluation of Herbal Face Serum - Gadekar Shital Rajendra; Bhalke Rasika Dnyandeo; Nagare Vidya Bhausaheb; Gadekar Monika Kishor; Wagh Anuradha Dattu; Giri Mahendra Ashok (Asian Journal of Pharmaceutical Research and Development, 2026)
This study aimed to develop and evaluate a polyherbal face serum containing guava leaf extract for skincare applications. Nine formulations (F1–F9) were prepared using suitable herbal and cosmetic ingredients and assessed for their physicochemical properties, including appearance, homogeneity, pH, viscosity, washability, and stability.All formulations exhibited good appearance, smooth texture, and acceptable consistency. The pH value was 5.4 within the suitable range for skin application, indicating good compatibility. Washability testing showed that the formulations could be removed easily without leaving any residue on the skin.Stability studies were conducted under room temperature and freezer conditions. F9 formulation remained physically stable throughout the study period, whereas a few batches showed instability under freezer conditions. Among all the formulations, F9 was identified as the optimized batch due to its excellent homogeneity, easy washability, appropriate viscosity (1910 cp), and superior stability. No noticeable changes in colour, odour, pH, or consistency were observed in F9 during the stability study.The findings demonstrated that the developed polyherbal face serum possesses desirable quality attributes, good physical stability, and satisfactory user acceptability. Therefore, the optimized F9 formulation has potential as an effective and stable herbal skincare product for regular facial care.